Optimization of work and rest hours for navigation officers on the ship - Simkuva H.; Purins A.; Mihailova S.; Mihailovs I.J. (SHS Web of Conferences, 2016)
The topic of the research as a whole is dedicated to studies of the work load of navigation officers and, consequently, is related to the current international research on the quality of working life. Issues of seafarers' working time are very topical because in recent years the load of navigation officers has significantly increased, either due to increase in shipping intensity, or in the context of the new international maritime law, for example, compliance with the requirements of the ISM CODE (International Management safety Code), THE ISPS (The International Ship and Port Facility Security Code). Irregularities are observed in practice of the seafarers' working hours and rest hours, and even the mismatch, as presented in the port of inspection materials. This article is intended to assess the 2nd and 3rd Officer's load compliance with the regulatory enactments for the work and rest regime to develop proposals to load optimization. Load analysis of Navigation officers is based on international maritime regulations that determine the work and rest regime on ships STCW (The International Convention on Standards of Training, Certification and Watchkeeping for Seafarers), MLC (Maritime Labour Convention). In the article, concrete data is used from the research, which was conducted 18 months on the Handy type of tanker from July, 2012 till December, 2013 in the real time mode. In the article is also concrete data used from 340 survey respondents, which reflects the views of the navigation officers on violations of the work and rest regime on the ship and the fatigue issue.